Ultrasonographic Measurement of the Biceps Femoris Long‐Head Muscle Architecture. (13th October 2017) - Freitas, Sandro R.; Marmeleira, João; Valamatos, Maria João; Blazevich, Anthony; Mil‐Homens, Pedro
Abstract : Objectives: Biceps femoris long‐head architectural assessment using ultrasonography (US) has not been previously described in detail for both acquisition (image capture) and digitization (image measurement) processes, and the effect of the US window width is unknown. This study aimed to describe the reliability and test‐retest minimum detectable difference of US‐based biceps femoris architectural measurements. Methods: Muscle length was determined by marking the muscle‐tendon junction distances. Sonograms were acquired with a 6‐cm image width and cropped for a 3‐cm width in 3 assessments (n = 20 adults). Intra‐ and inter‐rater reliability rates were determined for both image (3‐ and 6‐cm widths) acquisition and digitizing processes separated and together (within session) for the biceps femoris fascicle length, fascicle angle, and muscle thickness measurements using intraclass correlation coefficients (ICCs) and Pearson ( r ) correlation coefficients. Results: Muscle length was measured with high intra‐rater (ICC = 0.93; r  = 0.92) and inter‐rater (ICC = 0.90; r  = 0.90) reliability. Intra‐rater (coefficient of variation, 0.2%–1.8%) and inter‐rater (ICC = 0.79–0.99; r  = 0.80–0.99) digitizing reliability rates were high. High intra‐rater (ICC = 0.79–0.95; r  = 0.79–0.95) and moderate‐to‐high inter‐rater (ICC = 0.51–0.92; r  = 0.70–0.93) session reliability rates were found for all architectural parameters for 6‐ and 3‐cm images (intra‐rater ICC = 0.77–0.93; r  = 0.79–0.93; inter‐rater ICC = 0.63–0.98; r  = 0.90–0.98). The inter‐rater session reliability rates for both image acquisition and digitizing processes were higher for 6‐cm images (ICC = 0.65–0.86; r  = 0.67–0.87) than 3‐cm images (ICC = 0.28–0.93; r  = 0.67–0.93). The minimum detectable differences for the 6‐cm images were 8.4 mm, 1.5 °, and 1.6 mm for fascicle length, fascicle angle, and muscle thickness, respectively. Conclusions: Ultrasonography can be used to reliably assess midmuscle architecture of the biceps femoris muscle when the same rater performs image acquisition and digitization.